Selecting the right search term in query-based systems for deduplication - Jele, Harald (2021)
Essentially three approaches could be identiﬁed when choosing a proper search term to detect bibliographic duplicates. Stop words are excluded in all of them, then (1) just the ﬁrst term of an entry will be selected or (2) that term is selected, which produces the smallest number of hits or ﬁnally (3) that term will be used, which has a certain number of hits below a deﬁned threshold. These three procedures are compared with each other here. The results derive from series of measurements done with bibliographic data from the Austrian Central Catalog.